PEMAHAMAN TEKSTUAL DAN KONTEKSTUAL LARANGAN MENAFSIRKAN AL-QUR'AN DENGAN AL RA‘Y - Anisatun Muthi'ah (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2018)
Speaking about hadith, it will surely arrive at the issue that not all traditions in the Qat'iy al-Wurud are partially Zanniy al-Wurud, so the hadiths need to be re-examined in its curiosity. This paper examines the prohibited hadiths of interpretation of the Qur'an with the words and the study of this material can not be separated from the study of hadith tradition. In the hadith of the prohibition interpretation of the Qur'an with the word of the hadad is hasan. While the related directives are only available to Sunan al-Turmuzi, Sunan Abu Dawud and Musnad Ahmad bin Hanbal. As for the meaning of al-Ra'y which is required in the hadith is an interpretation which is based solely on reasoning without considering the history or methods or knowledge related or not in accordance with the principles of syar'i is something very different between interpreting the Qur'an with ra'yu (bi al-Ra'y) with the interpretation of bi al-Ra'yu which in its interpretation is dominated by intellect but remains in the frame of syar`i.